THE ROLE OF ACCOUNTING INFORMATION SYSTEMS, THREATS AND CONTROL STEPS IN FACING GLOBAL MARKET COMPETITION IN PT. XYZ - Cahyaningsih Kristilestari, Caecilia (Dinasti Publisher, 2019)
Currently the global market is a good and attractive choice for companies to develop themselves, but it is not easy to be able to penetrate the global market let alone to survive in it. The fact that is mostly found in the field is that many companies cannot survive and are able to compete successfully in the global market. Companies that enter the global market must be able to face a competition or competition. In efforts to deal with global market competition, many businesses can be done by companies, one of which is by using information systems. It should also be noted that information systems are not only a solution, but can also be a threat to companies when their control systems are not properly implemented. Then there needs to be an adequate and ready control system in the face of threats. The purpose of the research and writing of this paper is to find out about the use of accounting information systems their role in dealing with global market competition, including the threats that accompany and how to control them within the company. For this information system, the author tries to explain the possible threats, as well as design controls for mitigating these threats. The author uses the name PT.XYZ to describe the existence of the company. The research method used is a qualitative method, the writer tries to provide an explanation using analysis of various sources of literature.